Bacterial Community Dynamics in Kumamoto Oyster Crassostrea sikamea Hatchery During Larval Development - Dai, Wenfang; Ye, Jing; Liu, Sheng; Chang, Guangqiu; Xu, Hongqiang; Lin, Zhihua; Xue, Qinggang (Frontiers in microbiology, 2022)
Increasing evidence indicates that microbes colonized in early life stages have a long-term effect on animal wellbeing in later life stages. Related research is still limited in aquatic animals, particularly in bivalve mollusks. In this study, we analyzed the dynamics of the bacterial composition of the pelagic larval stages (fertilized egg, trochophore, D-stage, veliger, and pediveliger) and the sessile postlarval stage (spat) of Kumamoto oyster ( Crassostrea sikamea ) and their relationships with the rearing water bacterioplankton in a hatchery by using Illumina sequencing of bacterial 16S rRNA gene. Both bacterioplankton and larval bacterial communities changed greatly over larval development, and the two communities remarkably differed ( r = 0.956, P < 0.001), as highlighted by the differences in the dominant taxa and bacterial diversity. Ecological processes of larval bacterial communities were measured by abundance-unweighted and abundance-weighted standardized effect sizes of the mean nearest taxon distance (ses.MNTD). The unweighted ses.MNTD analysis revealed that the deterministic process constrained the larval bacterial assembly, whereas the weighted ses.MNTD analysis showed that larval bacterial composition was initially governed by stochasticity and then gradually by determinism in the later stages. SourceTracker analysis revealed that the larval bacteria were primarily derived from an internal source, mainly from larvae at the present stage. Additionally, the abundances of larval bacterial-mediated functional pathways that were involved in the amino acid, energy, lipid and carbohydrate metabolisms significantly altered with the larval development. These findings suggest that bacteria assemble into distinct communities in larvae and rearing water in the hatchery system, and the dynamics of bacterial community composition in larvae is likely associated with larval developmental stages.